Double-Hit Primary Plasma Cell Leukemia with IGH/MYC and IGH/CCND1 Translocations - Yasumi, Masato; Endo, Takaya; Sata, Hiroshi; Karasuno, Takahiro (Case Reports in Hematology, 2020)
Primary plasma cell leukemia (pPCL) is an aggressive variant of multiple myeloma (MM). Immunoglobulin heavy chain (IgH) translocations are found in a majority of pPCL cases, supporting a central relation to pathogenesis of pPCL. However, two independent IgH translocations are barely detected at the onset of pPCL, and their significance is yet to be elucidated. Here, we report a case of an aggressive pPCL with simultaneous IGH/MYC and IGH/CCND1 translocations. A 73-year-old man was referred to our hospital with back pain and diagnosed as having pPCL with more than 50% circulating plasma cells. Cytogenetic analysis revealed 47, Y, t (X; 8;14) (q24; q24; q32), t (11; 14) (q13; q32), and +18. IGH/MYC and IGH/CCND1 translocations were confirmed by fluorescence in situ hybridization analysis. Bortezomib and dexamethasone treatment achieved rapid elimination of peripheral malignant plasma cells, and the patient maintained a partial response for 18 months. After biological relapse, he received salvage therapy with ixazomib, lenalidomide, and dexamethasone, followed by pomalidomide and dexamethasone, and exhibited stable disease for an additional 14 months. Although IGH/MYC translocation in association with dysregulation of antiapoptotic pathway leads to worse prognosis in lymphomas, the novel agent-based regimen showed good efficacy, suggesting that IGH/MYC plays a different role in the pathogenesis of MM. IGH/CCND1 and IGH/MYC translocations may have contributed to abrupt onset of pPCL in this case.